Fostering Innovative Work Behavior through Job Autonomy and Employee Work Passion: Moderating Role of Communication Climate - Arifin, Nur Nisya Athirah Binti Mat; Salleh, Rohani Bt; Saleem, Muhammad Shoaib (Business Management and Strategy, 2024)
In today’s rapidly evolving business landscape, employees’ innovative work behavior (IWB) stands out as a fundamental factor in organizational success. Despite its critical importance, there remains a gap in understanding and measuring IWB, particularly within the branch of research and development (R&D) organizations. This study seeks to address this gap by exploring the relationships between communication climate, job autonomy, employee work passion, and innovative work behavior among employees in Malaysian R&D organizations through a sample of 325 respondents. By using a quantitative approach, this research utilized surveys to collect data from employees working within Malaysian R&D organizations. The sample was carefully selected to cover various sectors within R&D. The data collection process relied on the Innovative Work Behavior (IWB) scale. The analysis of the survey findings uncovers relationships between communication climate, job autonomy, work passion, and innovative work behavior within Malaysian R&D contexts. The research reveals significant correlations among these variables, offering valuable insights into the factors influencing employees’ inclination toward innovation. This study holds substantial implications for both scholars and practitioners in the fields of organizational behavior and management. By explaining the drivers of innovative work behavior within R&D organizations, this research provides actionable insights for nurturing a culture of innovation and enhancing organizational effectiveness.